#TITLE_ALTERNATIVE# - Swesty (NIM 15303011), Chandra
ABSTRACT: Based on the last research, about 28,84percent Bandung resident treat their domestic waste by open burning, because of the less services from PD.Kebersihan. It is hard process to get complete combustion in open burning of domestic waste. Unfortunately, the incomplete combustion will cause some air pollution such as CO and HC.There are two CO forming mechanisms in combustion, first the lean mixture between oxygen and the material which is burned and the second is the forming of CO in high temperature of combustion, above 2000 K. In other hand, CH4 can be produced because of insufficient combustion temperature, so the complex hydrocarbon of waste is not degradable as its natural habit. There are five parameters which affect combustion process; those are combustion temperature, air supply (oxygen) for the combustion, material for combustion, contact time and turbulence. Emission factor is a representative value which shows the pollutant amount which is released by source pollution unit. The purposes of this research is to calculate the amount of emission factor for CO and HC (as CH4) which is produced from domestic waste open burning and to find out its correlation between waste characteristic and the combustion condition. Thirty samples were taken randomly from the Bandung City. The combustion simulation was held in mini incinerator, single chamber, without air pollution control. The amount of CO and CH4 concentration were measured continually with auto emission analyzer during the combustion. Based on the research, the amount of CO and CH4 emission tend equal with organic mass fraction, waste density, waste water content and tend for having inverse relations with the an organic mass fraction and combustion temperature. Open Burning Test Facilities (OBTF) method which written in AP-42 document by US-EPA, is the used method to calculate the emission factor in this research. From this research, the emission factor per wet waste mass for CO is 230,81 g/kg and HC (as CH4) is 11,56 g/kg.